Influence of Sr Doping on Magnetic and Magnetocaloric Properties of Nd0.6Sr0.4MnO3 - Thi Anh, Ho; Huyen, Nguyen Ngoc; Thang, Pham Duc (VNU Journal of Science: Mathematics - Physics; Vol 36 No 1, 2020)
Nd 0.6 Sr 0.4 MnO 3 sample was fabricated by a solid-state reaction method and its magnetic, magnetocaloric properties were investigated. The Curie temperature, T C , at which a ferromagnetic-paramagnetic transition occurred was found to be of about 270 K. An analysis using the Banejee’s criterion of the experiment results for magnetization as a function of temperature and magnetic field and the universal curves of the normalized entropy change versus reduced temperature indicated that the sample undergo the second-order magnetic phase transition. Furthermore, the maximum magnetic entropy change that occurred near T C , measured at a magnetic field span of 50 kOe was found to be of about 6.0 J/kg.K, corresponding to a relative cooling power of 250 J/kg. These values are comparable to those of other manganites.